AN ISSUE OF INTELLIGENT ROAD TRANSPORT IN KAZAKHSTAN - Kairatolla Abishev; Ruslan B. Mukanov; Asylbek Zh. Kasenov; Almagul N. Baltabekova (Acta Polytechnica CTU Proceedings)
The article reviewed the road transport sector of the Republic of Kazakhstan and found a significant role in ensuring road transport of freight and passengers. Shown needs to improve the work of transport-communication complex of the Republic of Kazakhstan on the basis of using the latest information and communication technologies. Described advantages of realization of several intellectual transport technologies. Presented modern level of using satellite navigational systems on the automobiles, in addition written some automation and informational aspects of controlling transport processes. Also presented measures to solve technological rearmament problem of the Republic of Kazakhstan.